Meningkatkan Akhlakul Karimah Anak Usia Dini Melalui Metode Pembiasaan - Isman Efendi Limbong; Isropil Siregar (Al-Ulum: Jurnal Pendidikan Islam, 2022)
Morality can fix all the ugliness of appearance and deceptive external forms. So that he becomes an interpreter for what is hidden within a person. Actually, when the word "morals" is mentioned, it also includes all forms of morality. However, over time some of the morals have become abilities, so the good and the bad turn into part of the depths of our character. That is why the dichotomy of the terms "good morals" and "bad morals" appears. Allah draws our attention to the Allah’s Messenger with his very high morals and with his very high spiritual features, in other words, he asks us to see the Allah’s messenger with his morals which is the pinnacle of creation and the end of its ultimate purpose and meaning. This explains the character of the Prophet which is directly proportional to the depth of religion, the life that is compounded with it, and the implementation of the teachings of the Qur'an without flaws. On the other hand, it reminds us that the morals of the Prophet Muhammad are morals that have divine roots, the Qur'an. The character of the Prophet, which is qur'aniyah, deep, and reflects the breadth of God, cannot be compared with any moral system. His very noble character is also beyond human knowledge. That is why Allah uses the word "Khuluq" when referring to the morals of the Prophet Muhammad. It shows clearly that the Allah’s Messenger (PBUH) had no equal among mankind, both those who lived before him and after him. The purpose of this paper is that if you read it, it will certainly create a new influence that can move the soul to bring about great deeds. And many people are driven to do great deeds from reading the stories of great people. What we say in the "habits" about emphasizing the soul to do actions that have no meaning except to subdue the soul and give charity with daily actions with the intention of accustoming the soul to remain obedient, and maintaining the power of repulsion so that good invitations are accepted and bad ones are rejected. What is more important is to encourage moral education to oblige him to do good deeds for the public, which he always pays attention to and becomes the goal he must work on so that the results of these goals are many and people can choose according to what is in accordance with their wishes and joints. More about this source textSource text required for additional translation information.